Nollvisionsslinga i Trollhättan : före- och efterstudier av trafikantbeteenden med fokus på barn och äldre - Johansson, Charlotta (Luleå tekniska universitet, Arkitektur och vatten, 2002)
The Traffic Engineering Division at Luleå University of Technology has been commissioned by the fund Skyltfonden of the Swedish National Road Administration to evaluate the construction of the Vision-Zero Loop in Trollhättan. The primary aim is to collect background material for how the road administration's guidelines should incorporate the needs of children, elderly and handicapped users. This report presents results from observations of road-user behaviour at three locations in Trollhättan. Two of the sites are intersections along the Vision-Zero loop and the third one is a control site that was not reconstructed. At the intersections at the Vision-Zero Loop the zebra crossings were reconstructed to areas provided for pedestrians to cross the street but not marked as zebra crossings, in Swedish "gångpassager". Construction of the Vision-Zero Loop started in the summer of 2000 and was finished during the first half of 2001. The Loop contains urban as well as rural segments. This report covers only urban sections. The effect of tougher national regulation regarding drivers' obligations to yield to pedestrians, which took effect on May 1, 2000, has also been studied. The methodology used for these studies is been based on data collection through video recordings. Behaviour of pedestrians, bicyclists and drivers interacting with pedestrians and bicyclists is coded from video analysis. Traffic conflicts and other near misses with pedestrians and bicyclists are especially analysed Godkänd; 2002; 20080919 (andbra)